EFESIENSI BIAYA OPERASIONAL TERHADAP PENINGKATAN LABA PADA BANK RAKYAT INDONESIA (PERSERO) Tbk DI KABUPATEN ENREKANG - Ismail Badollahi; mega Zintia Z (INVOICE : JURNAL ILMU AKUNTANSI, 2019)
The research was conducted at Bank Rakyat Indonesia (BRI) KCP Unit Baraka Enrekang Regency which aims to determine the efficiency of operational costs to increase profits at BRI. Then the sample examined is the financial report data from 2013 - 2017. Using descriptive analysis techniques and simple linear analysis techniques. From the analysis results found the regression equation formula Y = 3017464,086 + 0.936X. stated that when operating expenses were 0, the increase in profit was 3017464,086 and where each increase in one unit of operating expenses would cause an increase in profit of 0.936. T test and F test both show that there is an influence between operational burden on profit increase which is shown that T table and F table are smaller than T arithmetic and F arithmetic with the formulation Ha is accepted and H0 is rejected.T test and F test both show that there is an influence between operational burden on profit increase which is shown that T table and F table are smaller than T arithmetic and F arithmetic with the formulation Ha is accepted and H0 is rejected.